Comparative Analysis of Endovascular Stroke Therapy Using Urokinase, Penumbra System and Retrievable (Solitare) Stent - Choi, Jae-Hyung; Park, Hyun-Seok; Kim, Dae-Hyun; Cha, Jae-Kwan; Huh, Jae-Taeck; Kang, Myongjin (Journal of Korean Neurosurgical Society, 2015)
Higher reperfusion rates have been established with endovascular treatment for acute ischemic stroke patients. There are limited data on the comparative performance of mechanical thrombectomy devices. This study aimed to analyse the efficacy and safety of the stent retriever device (Solitaire stent) by comparing procedure time, angiographic outcome, complication rate and long term clinical outcome with previous chemical thrombolysis and mechanical thrombectomy using penumbra system. A retrospective single-center analysis was undertaken of all consecutive patients who underwent chemical thrombolysis and mechanical thrombectomy using Penumbra or Solitaire stent retriever from March 2009 to March 2014. Baseline characteristics, rate of successful recanalization (modified Thrombolysis in Cerebral Infarction score 2b-3), symptomatic intracerebral hemorrhage, procedure time, mortality and independent functional outcomes (mRS ≤2) at 3 month were compared across the three method. Our cohort included 164 patients, mechanical thrombectomy using stent retriever device had a significant impact on recanalization rate and functional independence at 3 months. In unadjusted analysis mechanical thrombectomy using Solitaire stent retriever showed higher recanalization rate than Penumbra system and chemical thrombolysis (75% vs. 64.2% vs. 49.4%, p=0.03) and higher rate of functional independence at 3 month (53.1% vs. 37.7% vs. 35.4%, p=0.213). In view of the interrelationships between all predictors of variables associated with a good clinical outcome, when the chemical thrombolysis was used as a reference, in multiple logistic regression analysis, the use of Solitaire stent retriever showed higher odds of independent functional outcome [odds ratio (OR) 2.62, 95% confidence interval (CI) 0.96-7.17; p=0.061] in comparison with penumbra system (OR 1.57, 95% CI 0.63-3.90; p=0.331). Our initial data suggest that mechanical thrombectomy using stent retriever is superior to the mechanical thrombectomy using penumbra system and conventional chemical thrombolysis in achieving higher rates of reperfusion and better outcomes. Randomized clinical trials are needed to establish the actual benefit to specific patient populations.